Pengaruh Disiplin Kerja, Pelatihan Dan Lingkungan Keja Fisik Terhadap Kinerja Karyawan PT. XYZ - Arista Kumala Qotrun Nanda; Maulidyah Amalina Riqzi; Nur Cahyadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the work discipline, training and physical work environment at PT. XYZ. The object of this research is 84 employees of PT. XYZ, the method used in sampling is Saturated Sampling Method (All Populations are sampled). The data analysis technique uses multiple linear regression analysis. The results of multiple linear regression analysis prove that the work discipline, training and physical work environment have a significant effect on the performance of PT. XYZ.